2022
DOI: 10.1097/md.0000000000028760
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative embolization and excision of vagal schwannoma with rich vascular supply

Abstract: Rationale: Schwannomas are benign tumors wrapped in the nerve sheath and can originate from the myelin sheath of the cranial nerve. In previous literature reports, most of the tumors were solid tumors, which can be removed only by surgery. This case report describes a unique case of vagal schwannoma, which, unlike previous cases, involves a dominant arterial supply, and discusses the pre-operative evaluation, relevant radiographic findings, and surgical process of the case in detail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Interestingly, several studies have shown that understanding the eccentric growth pattern of the tumor and the anatomical features of the recurrent laryngeal and non-laryngeal reflexes can help surgeons to protect nerves as much as possible to preserve good vocal function after surgery [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have shown that understanding the eccentric growth pattern of the tumor and the anatomical features of the recurrent laryngeal and non-laryngeal reflexes can help surgeons to protect nerves as much as possible to preserve good vocal function after surgery [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%